Literacy culture in DKI Jakarta elementary schools: An analysis based on school accreditation data - Dinihari, Yulian; Musringudin, Musringudin; Boeriswati, Endry (Universitas Ahmad Dahlan, 2026)
This study examines the implementation of literacy culture and learning quality in public elementary schools across DKI Jakarta. In this study, literacy culture is defined as the institutional integration of reading and writing practices, supportive learning environments, aligned assessment, and school facilities that sustain literacy-oriented instruction. Using data from 195 accredited schools, the research analyzes seven key indicators: higher-order thinking skills, student assessment, remedial and enrichment programs, enjoyable learning facilities, literacy integration, classroom environment, and infrastructure optimization. Accreditation documents were used not as direct measures of students’ literacy outcomes, but as institutional indicators reflecting the extent to which schools embed literacy-supporting practices in teaching and school management. The results show that most schools have implemented structured literacy programs and performance-based assessments, with 97.4% achieving high literacy integration. However, disparities remain in interactive learning environments and differentiated instruction, as only 46.2% met the criteria for enjoyable facilities and 69.7% for remedial and enrichment efforts. Qualitative analysis using NVivo identified dominant themes such as learning, literacy, and comfort, indicating school priorities. The study highlights the need for holistic improvement strategies, including technology integration, teacher training, and infrastructure support, to ensure sustainable literacy development and equitable access to quality education in urban settings. These findings show that high institutional literacy integration does not automatically indicate equal quality across all supporting dimensions, especially in enjoyable learning facilities and remedial-enrichment practices.